Small molecules in idiopathic inflammatory myopathies: a systematic review and a multicenter case series about Janus kinase inhibitors and apremilast - Chiara Rizzo; Silvia Grazzini; Edoardo Conticini; Hector Chinoy; Roberto D’Alessandro; Federica Camarda; Luca Cantarini; Bruno Frediani; Giuliana Guggino; Lidia La Barbera (Reumatismo)
Objective. Idiopathic inflammatory myopathies (IIM) are rare autoimmune diseases that primarily affect striated muscles; skin, joints, and lungs may be involved with different degrees of severity. Traditional treatment relies on high-dose glucocorticoids and conventional synthetic disease-modifying antirheumatic drugs.